Correlation between Jump Performances and Phases of Sprinting in Indonesian Sprinters. (March 2017) - Wibowo, R; Abdullah, C U
Abstract: The purpose of this study was to determine the relationships jump performances and phases of sprinting in indonesian sprinters. Nine national level male sprinters participated in this study at the competitive phase. The jumping performance including standing broad jump (SBJ), vertical jump (VJ), and standing single leg hop (SSLH). Phase of sprinting determined used 30 metre sprint test for acceleration phase (AP) and determined maximal speed (MS) used flying 30 metre test. Normally distributed data were analysed using Pearson's correlation coefficients. The results show that strong correlation between SBJ and AP (r = -0, 691; p=0.039). Moderate correlations were found between VJ and AP (r = -0, 565; p = 0.113), and strong correlation between SSLH and AP (r = -0, 729; p = 0, 026). There are moderate correlation between SBJ and MS (r = 0, 420; p = 0, 260) and between VJ and MS (r = 0, 537; p = 0, 136) and strong correlation SSLH and MS (r = 0, 720; p = 0.029). Overall the findings of the present study indicated that there are correlation between jumping performance, AP and MS at competitive phase. SSLH showed stronger to predict AP and MS at competitive training phase. There appears to be a relationship between jump performance and phase of sprinting in this population, but more studies with bigger population are needed to confirm these results.